Application of Renewable Energy and Internet of Things on Retort Machine to Improve Sterilization Process Efficiency of Cakalang Fufu Fish - Arifmanuel Kolondam; Ficky Marchfirmanto Purba; Oldi Malfri Lambonan; Selvy R Kalele; Andreas Randy Wangarry (Eduvest - Journal of Universal Studies, 2025)
The conventional preservation process of fufu skipjack fish still relies on traditional smoking methods that depend on heat directly from combustion. These methods are less energy efficient, difficult to control in terms of temperature and time, and produce products with inconsistent quality and shelf life. This research was conducted to develop a fufu skipjack sterilization system based on an integrated retort machine with boilers and ovens supported by renewable energy and the Internet of Things (IoT). The system is designed to improve energy efficiency, process stability, and extend product life. Renewable energy is obtained from solar cells used to drive the blower in the oven, activate the solenoid valve between the boiler and the retort, and support a microcontroller-based control system. IoT technology is integrated to monitor temperature and pressure in real time, control the oven blower, and automatically set the solenoid over the internet network. The test results show that this retort system can maintain a sterilization temperature of up to 121°C stably, reduce energy consumption by up to 25% compared to conventional methods, and extend the shelf life of fufu skipjack fish by more than two times without degrading organoleptic quality. The application of renewable energy and IoT in this integrated retort machine proves its effectiveness in improving process efficiency, production reliability, and the sustainable export potential of local processed fish products.